Advancements in magnetic nanoparticle-based biosensors for point-of-care testing - Wang, Miaomiao; Jin, Lian; Hang-Mei Leung, Polly; Wang-Ngai Chow, Franklin; Zhao, Xiaoni; Chen, Hui; Pan, Wenjing; Liu, Hongna; Li, Song (Frontiers in Bioengineering and Biotechnology, 2024)
The significance of point-of-care testing (POCT) in early clinical diagnosis and personalized patient care is increasingly recognized as a crucial tool in reducing disease outbreaks and improving patient survival rates. Within the realm of POCT, biosensors utilizing magnetic nanoparticles (MNPs) have emerged as a subject of substantial interest. This review aims to provide a comprehensive evaluation of the current landscape of POCT, emphasizing its growing significance within clinical practice. Subsequently, the current status of the combination of MNPs in the Biological detection has been presented. Furthermore, it delves into the specific domain of MNP-based biosensors, assessing their potential impact on POCT.By combining existing research and spotlighting pivotal discoveries, this review enhances our comprehension of the advancements and promising prospects offered by MNP-based biosensors in the context of POCT. It seeks to facilitate informed decisionmaking among healthcare professionals and researchers while also promoting further exploration in this promising field of study.